2022
DOI: 10.3390/nu14245336
|View full text |Cite
|
Sign up to set email alerts
|

Can Mild-to-Moderate Iodine Deficiency during Pregnancy Alter Thyroid Function? Lessons from a Mother–Newborn Cohort

Abstract: Severe iodine deficiency during pregnancy has substantial hormonal consequences, such as fetal brain damage. Data on the potential effects of mild-to-moderate iodine deficiency on the thyroid function of pregnant women and their newborns are scarce and divergent. We investigated the association between iodine intake in pregnancy and maternal and neonatal thyroid function in a region with mild-to-moderate iodine deficiency. Pregnant women’s iodine status was evaluated using an iodine food frequency questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Moreover, the estimated iodine from ICS was 62 µg/day, although the current study participants reported that the majority of ICS they consumed contained 220 µg of iodine per tablet. The reason for this gap is the inconsistent ICS intake values reported by the ICS consumers who participated in our study, resulting in a weighted lower estimate of iodine intake from ICS (Table 2) [16]. In light of this, safe and mandatory iodine prophylaxis in Israel should be urgently implemented.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Moreover, the estimated iodine from ICS was 62 µg/day, although the current study participants reported that the majority of ICS they consumed contained 220 µg of iodine per tablet. The reason for this gap is the inconsistent ICS intake values reported by the ICS consumers who participated in our study, resulting in a weighted lower estimate of iodine intake from ICS (Table 2) [16]. In light of this, safe and mandatory iodine prophylaxis in Israel should be urgently implemented.…”
Section: Discussionmentioning
confidence: 84%
“…The median Tg value determined was 18 µg/L; this is above the cutoff considered for iodine sufficiency in pregnancy, indicating iodine insufficiency (>13 µg/L) in this study population [25]. Detailed nutritional, hormonal, and clinical characteristics of the study population were previously described [16].…”
Section: Maternal Nutritional Hormonal and Clinical Characteristicsmentioning
confidence: 85%
See 1 more Smart Citation
“…This study was a longitudinal prospective cohort study; its methods have previously been described in detail [ 16 ]. In brief, the study was conducted during the period of June 2018 to April 2020.…”
Section: Methodsmentioning
confidence: 99%
“…All in all, 202 pregnant women participated in the study. A detailed description of the screening procedure, study sample, and follow-up flow chart can be found elsewhere [ 16 ]. The BUMCA’s ethical committee approved the study (no’ 001-17-BRZ dated 7 August 2017).…”
Section: Methodsmentioning
confidence: 99%